The clash of political forces in the gaps region during the second half of the 5th/11th century (448-491 AH/1056-1098 )AD) - Muray, Sami; Hasan, Ghada; Ali, Ahmad (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
In the second half of the 5th/11th century, Armenians were among the main forces competing for sovereignty and influence in the Levantine gaps region of its Levantine and Aljazria parts, In that region, the Armenians found the appropriate geographical area to establish their alternative state for their ephemeral kingdom in Greater Armenia, But their ambitions collided with the Seljuk Turkmen ambitions on the one hand and the Byzantine on the other, to dominate that region, which has a strategically important geostrategic location for both sides, This has fuelled the conflict situation in that region, and it is therefore imperative for the Armenians to adapt to that situation from the power struggles around them to control the gabs region, So their policy varied and changed towards those forces and swung between subordination and dependence, hostility and confrontation, it was an addition to other factors related to the nature of the Seljuk Turkmen invasion on the one hand and to the turbulent conditions that the Byzantine Empire was experiencing on the other hand, One of the things that brought the Armenians to safety, enabled them to declare their Armenian kingdom of Rubenian in the next century.